Melatonin induces drought tolerance by modulating lipoxygenase expression, redox homeostasis and photosynthetic efficiency in Arachis hypogaea L - Shreya, Sharma; Supriya, Laha; Padmaja, Gudipalli (Frontiers in Plant Science, 2022)
Melatonin (N-acetyl-5-hydroxy tryptamine), a multipotent biomolecule is well known for its ability to confer tolerance to several abiotic and biotic stresses. The regulation of melatonin-mediated drought tolerance in drought-distinguished varieties can be different due to discriminating redox levels. The present study was focused on assessing the effects of melatonin priming against polyethylene glycol (PEG)-induced stress with respect to the antioxidant system, photosynthetic parameters, lipoxygenase expression, JA and ABA levels in drought-sensitive (Kadiri-7) and drought-tolerant (Kadiri-9) varieties. Exogenous melatonin alleviated the drought stress effects in sensitive variety (Kadiri-7) by increasing the endogenous melatonin content with an improved antioxidant system and photosynthetic attributes. The primed stressed plants of the sensitive variety exhibited reduced expression and activity of the chlorophyll degrading enzymes (Chl-deg PRX, pheophytinase and chlorophyllase) with a concomitant increase in chlorophyll content in comparison to unprimed controls. Interestingly, melatonin priming stimulated higher expression and activity of lipoxygenase (LOX) as well as enhanced the expression of genes involved in the synthesis of jasmonic acid (JA) including its content in drought stressed plants of the sensitive variety. The expression of NCED3 (involved in ABA-biosynthesis) was upregulated while CYP707A2 (ABA-degradation) was downregulated which corresponded with higher ABA levels. Contrastingly, priming caused a decrease in endogenous melatonin content under drought stress in tolerant variety (Kadiri-9) which might be due to feedback inhibition of its synthesis to maintain intracellular redox balance and regulate better plant metabolism. Furthermore, the higher endogenous melatonin content along with improved antioxidant system, photosynthetic efficiency and LOX expression associated with the increased levels of JA and ABA in unprimed stressed plants of the tolerant variety (Kadiri-9) is pointing towards the effectiveness of melatonin in mediating drought stress tolerance. Overall, exogenous melatonin alleviated the adverse effects of drought stress in sensitive variety while having no add-on effect on drought stress responses of tolerant variety which is inherently equipped to withstand the given duration of drought stress treatment.